The support board: treatment without transfer / Tun Yasmin Iffah Mohd Suria Affandi - Mohd Suria Affandi, Tun Yasmin Iffah; Omar Khattab Khan, Aminda Faizura; Ismail, Mohd Isyrafuddin; Ab Sukor, Hany Suraya; Ahmad, Mas Suryalis (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
In providing care for patients with special healthcare needs, physical access to the dental chair is imperative for better treatment provision. However, this has always been a challenge especially for patients who are physically impaired like wheelchair users. Most situations would require patients to be transferred from their wheelchair to the dental chair which poses multiple risks and potential harm to the patient, as well as the dental staff or caregiver. This innovation aims to enable dental treatment to be provided without requiring the patient to be transferred thus minimizing injury risk for all stake holders. Unlike expensive reclining platforms with headrests, The Support Board design provides a backrest that seamlessly integrates with the patient’s own wheelchair and allows the patient to lean comfortably while receiving dental care. Besides that, this posture-supporting device also provides comfort to the patients, as the adjustable head rest may be able to cater to individuals of different heights. Therefore, this innovation will improve the accessibility for individuals who rely on wheelchairs in obtaining dental treatment. In addition, this innovation minimizes the threat of occupational hazards that could occur when transferring patients from the wheelchair to the dental chair. This solution for wheelchair users within dental practice settings has a high potential for commercialization as the support board fits the standard-sized wheelchair, is lightweight and easy to store due to its size and shape and is made of materials that can be sterilized using hospital-grade disinfectant wipes. The ability for this innovation to enhance accessibility for wheelchair users even to obtain treatment in home settings and prevent occupational hazards is highly marketable, while allowing for better dental management of patients with special healthcare needs to dental care without compromising their comfort.